When red means go: Non‐normative effects of red under sensation seeking. Issue 1 (6th May 2016) - Mehta, Ravi; Demmers, Joris; van Dolen, Willemijn M.; Weinberg, Charles B.
Abstract: Although previous research has identified red as the color of compliance, the current work proposes that this effect of red may not hold under high sensation‐seeking propensity conditions. It is argued that the color red has the capability to induce arousal, which in turn has been shown to enhance a person's default tendencies. Further, because high sensation seekers have a higher tendency to react, the exposure to the color red for these individuals will increase reactance and thereby non‐compliant behavior. One field study and two lab experiments provide support for this theorizing. The first experiment, a field study, examines prank‐chatting incidences at a child helpline and shows a positive effect of red on such non‐compliant behavior. Experiment 2 confirms this finding in a controlled lab setting and shows that when one has a high sensation‐seeking propensity, the color red positively affects one's attitude towards non‐compliance. The final study illuminates the underlying process and explicates the role of arousal and reactance in the color–non‐compliance relationship. Both theoretical and practical implications are discussed.